Dynamic response of saddle membrane structure under hail impact. (1st July 2020) - Liu, Changjiang; Deng, Xiaowei; Liu, Jian; Peng, Tianju; Yang, Shaopeng; Zheng, Zhoulian
Highlights: The contact time between hail and membrane is related to the membrane stiffness and impact velocity. The resistance to external loads is not only related to the pretension but also the rise-span ratio. The relaxation effect due to the hail may significantly reduce the critical wind speed of membrane. Abstract: In this paper, the dynamic response of a typical four-point pretensioned saddle membrane structure under hail impact load is investigated by numerical simulations and experimental studies. Firstly, the initial shape of saddle membrane is obtained by form-finding analysis using the finite element analysis software ANSYS. The complex mechanical process of hail impact on the flexible membrane is simulated by LS-DYNA/Explicit dynamic analysis program, and the dynamic response of membrane, including displacement, velocity and acceleration, etc, is characterized. Then the experiment of saddle membrane under hail impact is carried out by applying the same loading conditions with the numerical analysis. The comparison between the numerical and experimental results shows good agreement, which verifies the reliability of the numerical simulations. It is discovered that the pretension relaxation induced by the hail impact may decrease the critical wind speed of membrane, and significantly increase the risk of membrane instability subject to hailstorm. Finally, the dynamic characteristics of typical four-point tensioned saddle membrane are summarized, which may provide reference for the design, construction and maintenance of membrane structures.